2011
DOI: 10.1016/j.rinim.2011.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization and phylogenetic analysis of two antimicrobial peptides: Anti-lipopolysaccharide factor and crustin from the brown mud crab, Scylla serrata

Abstract: AMPs are evolutional weapons, widely used by animals and plants in their innate immune system to fend off invading microbes. The present study reports characterization of a new ALF isoform (Sc-ALF; HQ638024) and the first crustin (Sc-crustin; HQ638025) from the mud crab, Scylla serrata. The full-length cDNA of Sc-ALF consisted of 477 bp with an ORF of 123 amino acids and a putative signal peptide of 26 amino acids. Sc-ALF had a predicted molecular weight (MW) of 11.17 kDa and theoretical isoelectric point (pI)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…Crustins have antibacterial properties, they must contribute to a greater or lesser extent in defence against bacterial infections, at least in decapods. However, the variable pattern in their expression after bacterial challenge is unlike than known for other arthropod antimicrobial peptides [33] .…”
Section: Crustinmentioning
confidence: 92%
“…Crustins have antibacterial properties, they must contribute to a greater or lesser extent in defence against bacterial infections, at least in decapods. However, the variable pattern in their expression after bacterial challenge is unlike than known for other arthropod antimicrobial peptides [33] .…”
Section: Crustinmentioning
confidence: 92%
“…The recombinant CrusSp was produced to assess its antimicrobial activities against Gram-negative bacteria, with the indication that CrusSp may be involved in the innate immunity of S. paramamosain. Interestingly, Afsal et al [37] successfully identified a new isoform of ALF, Sc-ALF, and first crustin, Sc-crustin, from the haemocyte of the S. serrata. On top of that, the nucleotides sequence of Sc-ALF was found to be 100% similar to ALF in S. paramamosain, which is almost similar to several AMP from other decapods crustaceans when tested with BLAST analysis.…”
Section: Antimicrobial Peptides In Mud Crabsmentioning
confidence: 99%
“…2 Since then, numerous ALF homologs have been identified and characterized from decapod crustaceans, including penaeid shrimp, [3][4][5][6] nonpenaeid shrimp, 7 lobsters, 8,9 crabs, and crayfish. [10][11][12][13] ALFs belong to the group of single-domain AMPs with a signal peptide at the N-terminal region followed by a conserved LPS-binding domain.…”
Section: Introductionmentioning
confidence: 99%